2019
DOI: 10.21273/hortsci14321-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Detached Strawberry Leaves for Anthracnose Disease Severity Using Image Analysis and Visual Ratings

Abstract: Inoculation of detached strawberry leaves with Colletotrichum species may provide an accurate, rapid, nondestructive method of identifying anthracnose-resistant germplasm. The purpose of this study was to statistically compare two methods (visual and image analysis) of evaluating disease severity of strawberry germplasm screened for anthracnose resistance. Detached leaves of 77 susceptible and resistant strawberry clones were inoculated with one Colletotrichum gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous research by Monteon-Ojeda et al (2017) found that extended incubation periods were negatively associated with disease severity and low incidence. In contrast, incidence positively correlated with disease severity-a positive correlation between spot diameter and disease severity (Miller-Butler et al, 2019).…”
Section: Resistance To Anthracnosementioning
confidence: 90%
“…Previous research by Monteon-Ojeda et al (2017) found that extended incubation periods were negatively associated with disease severity and low incidence. In contrast, incidence positively correlated with disease severity-a positive correlation between spot diameter and disease severity (Miller-Butler et al, 2019).…”
Section: Resistance To Anthracnosementioning
confidence: 90%
“…White leaf spots (Figure 5D) (Cérès Agricole, Red Gold of Africa, Mbidjoro Sustainable Living Environment, and KAFFO Farm); leaf yellowing (Figure 5E) (Cérès Agricole, Red Gold of Africa, BIO Farm of Lolodorf, and Bafoussam Farm), and whitish down on the upper and lower leaf surfaces (Figure 6F) (KAFFO Farm) were also recorded. Melinda [27], Baroncelli [28], Abd-El-Kareem [29], and Mykhailenko [30] attribute these black spot symptoms to anthracnose caused by Colletotricum acutatum or Colletotricum gloeosporioides, or Cercospora fragariae, and purple blight caused by Diplocarpon earlianum, while the common leaf spots are caused by Mycosphaerella fragariae. On the other hand, white leaf spots are thought to be the result of Ramularia grevilleana attacks [29] [30].…”
Section: Diseases Identified In Strawberries In the Fieldmentioning
confidence: 99%
“…The estimated severity of anthracnose symptoms in leaves was as follows: severity = (infected leaf area/total leaf area) × 100% (Miller-Butler et al, 2019).…”
Section: Screening Testmentioning
confidence: 99%